Peningkatan Pemahaman Siswa MA Nahdlatul Thullab Manggarwetan tentang Kewajiban Pelaporan Peristiwa Kependudukan - Endah Pujiastuti; Subaidah Ratna Juita; Albertus Heru Nuswanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Population event reporting is mandatory for all residents. Population event reporting aims to provide identity validity and legal certainty through population documents in every population event experienced by residents. In addition to being proof of the legality of various administrative matters, this reporting also plays an important role in the administration of the state. The obligation to report population events has not been properly understood by partners. This community service activity was carried out to overcome the partner's problem, namely the low understanding of MA Nahdlatut Thulab students about the obligation to report population events. The solution offered is to improve student understanding through legal counseling and measured discussions. This community service activity used lecture, discussion, and question-and-answer methods. As a result of the activity, students became more aware of population events, the obligation to report population events, how to report them, and the importance of reporting. There was an increase in student understanding before and after the activity was carried out.